Kokoda - Fitzsimons, Peter (Hachette Australia, 2008)
Storm clouds gather - Battle stations - Mud, mosquitoes, malaria and monotony - Sweating it out - Dynamic duo - Up the bloody track - Attack! - Strike-back! - Holding on - A weary way to go... - The Battle of Isurava - Gumption, guts and glory - Falling back - The Battle of Brigade Hill - The tide turns - To the bitter end. The book follows in the footsteps of the heroes and villains of the campaign - from the inexperienced but brave men of the 39th Battalion at the frontlines to the imperious generals like MacArthur and Blamey. Together with the soldiers, the reader climbs the neverending steep mountain ranges, digs in to defend the muddy positions in the native villages, charges forth into frenzied battle and follows the wounded's long, desperate trek back to safety. As well as bringing the ragged, bloody heroes of the Australian army alive, Kokoda gives the perspective of the crack Japanese troops and the extraordinary local people as well. Moving, gripping and exciting, the author has written a masterful account of this iconic campaign that will ensure all Australians can understand what a small band of Australian troops achieved high in the New Guinea jungle - and marvel at it. [Trove Books]